Parents' Experiences and Sexual Topics Discussed with Adolescents in the Accra Metropolis, Ghana: A Qualitative Study - Elizabeth AKu Baku; Isaac Agbemafle; Agnes Millicent Kotoh; Richard M. K. Adanu (Hindawi Limited, 2018)
Background. Traditionally, discussion about sexuality is subdued in proverbs and is earmarked for adults. However, adolescents also need information about their sexuality to make informed choices regarding sexual behaviours. This study, therefore, seeks to explore the experiences of parents discussing sexuality topics with adolescents in the Accra Metropolis, Ghana. Methods. This was a qualitative study that used focus group discussions (FGDs) and in-depth interviews (IDIs) to assess parents' experiences in discussing sexuality topics with adolescents. The FGDs, consisting of 8-12 parents each, were conducted for one "all fathers", then another "all mothers", and finally "fathers and mothers" groups. Parents who were not part of the FGDs were engaged in IDIs. The data was transcribed and analyzed manually. Results. Most of the parent-adolescent sexual discussions were based on physical changes, personal hygiene, abstinence, abortion, and saying "no" to forced sex. Parents discussed sexuality issues with adolescents to prevent them from premarital sex, pregnancy, and sexually transmitted infections. Parents sourced their knowledge about sexuality from books, television, radio, and personal experiences. Parents always seize opportunities such as television scenes to discuss sexual topics with their children. Although some parents expressed some level of comfort discussing sexual topics with adolescents, many still had difficulties explaining some terminologies related to sex. Preferentially, parents were protective of their girls than the boys when discussing issues on sexuality. Most parents received no sexuality education from their parents but a few reminisced precautionary advices on sex. Parents believed training on sexuality issues will help them to better discuss sexual topics with adolescents. Conclusions. Ghanaian parents preferentially discuss sex with their daughters as a protective tool against irresponsible sexual behaviours. Parents still have challenges discussing adolescent sexuality topics; hence equipping parents to effectively discuss such sensitive topics will improve adolescent reproductive health and sexual behaviour.